Carrying and Using Sharp Weapons in Public: Regulation, Challenges, and Reform - Sahrudin Sahrudin; Farhan Jiddan Saros; Raden Bagus Mochammad Ramadhan R.H; Taufik Rizki; Zalfa Rizqiya Shabriananda (CV. Pustaka Parawali, 2025)
The phenomenon of the use and possession of sharp weapons in public spaces in Indonesia, especially in Madura, has become a serious concern because it has the potential to pose a threat to public security and order. The tradition of carrying sharp weapons, such as celurit, is often associated with local culture but is also often misused in various criminal acts. This study aims to analyze regulations related to the possession and use of sharp weapons based on Emergency Law Number 12 of 1951 and assess the effectiveness of their implementation in the community, especially in the socio-cultural and security contexts. The research method used is a normative approach with legal analysis and literature study. The results show that although the regulation has regulated the prohibition of carrying sharp weapons in public spaces without a permit, its implementation still faces various challenges, including a lack of public understanding, diverse legal interpretations, and constraints in law enforcement. Cultural factors, such as the tradition of